Relational Leadership sebagai Pengalaman Hidup Karyawan: Studi Fenomenologi pada Outlet Ayam Uleg Cak Abit - Salma Faza; Nasharuddin Mas; Choirul Anam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This research explores the meaning of leadership in employee experiences at Ayam Uleg Cak Abit outlets in Malang City using a transcendental phenomenological approach. In the context of culinary organizations operating 24 hours without formal managerial structures, leadership is understood not merely as a structural position but as relational experiences shaping daily work life. This study involves six participants (two leaders and four employees) selected through purposive sampling, with data collected through in-depth interviews, non-participatory observations, and documentation. Data analysis follows Moustakas' (1994) four stages: epoche, phenomenological reduction, imaginative variation, and synthesis of meanings and essences. Findings reveal that employees perceive meaningful leadership through leader's direct presence, involvement in operational work, emotional support during high-pressure situations, and creating work environments valuing each employee's contribution. Leadership essence emerges through authentic relationships, consistent exemplary behavior, and sincere care in daily interactions rather than formal authority or hierarchical position. This research contributes to leadership theory by providing phenomenological perspectives and offers practical implications for developing more humanistic leadership practices in informal organizations. The study concludes that meaningful leadership in culinary outlets is built through trust, open communication, and ability to build significant relationships with employees.